Educational and wage risk: social insurance vs. quality of education - Dirk Schindler; Benjamin Weigert (Center for Economic Studies and ifo Institute (CESifo), 2008)
In this model of education, where individuals are exposed both to educational risk and to wage risk within the skilled sector, successful graduation depends both on individual effort to study and on public resources. We show that insuring the present risks is a dichotomic task: Wage risk is diversified ex post among the skilled by graduate taxation and skill-specific tuition fees. Educational risk of failure and inequality between skilled and unskilled workers are mitigated ex ante by enhancing the quality of education. The necessary expenditures are optimally financed by regressive tuition fees and the net revenue from the graduate tax.
Keywords: H21; I2; J2; 330; Human capital investment; educational risk; wage risk; learning effort; graduate taxation; regressive tuition fees; Bildungsinvestition; Bildung; Lohn; Risiko; Studienfinanzierung; Absolventen; Steuer; Sozialversicherung; Theorie